Implementation of Authentic Assessment in Science Learning at Indonesian Schools - Didik Setyawarno; Atik Kurniawati (Universitas Negeri Yogyakarta, 2018)
This article is intended for students of science education, science teachers and observers of science education. The article aims to discuss about authentic assessment in science teaching in schools. In addition, this article is associated with the implementation of the curriculum of 2013 in schools. Aspects reviewed in the article include: the concepts of authentic assessment, assessment in the curriculum of 2013, procedures of authentic assessment, and the application of authentic assessment in science learning. Readers after reading this article are expected to have an understanding of the concepts of authentic assessment, assessment in the curriculum of 2013, procedures in authentic assessment, and the application of an assessment of authentic in science learning.